2021
DOI: 10.1039/d1ra06986a
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting the electronic properties and contact types of graphene/F-diamane-like C4F2 van der Waals heterostructure: a first principles study

Abstract: We perform a first principles study to investigate the atomic structure, electronic properties and contact types of the graphene/F-diamane-like C4F2 heterostructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 75 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…F-diamane is a direct gap semiconductor with a valence band maximum (VBM) and a conduction band minimum (CBM) located at the Γ point. The band gap of 3.950 eV is similar to other results (3.938 eV, 15 4.03 eV 33,38 and 4.13 eV 12 ). After doping of N and B atoms, we find that the band structures of F-diamane are evidently modulated.…”
Section: Resultssupporting
confidence: 90%
“…F-diamane is a direct gap semiconductor with a valence band maximum (VBM) and a conduction band minimum (CBM) located at the Γ point. The band gap of 3.950 eV is similar to other results (3.938 eV, 15 4.03 eV 33,38 and 4.13 eV 12 ). After doping of N and B atoms, we find that the band structures of F-diamane are evidently modulated.…”
Section: Resultssupporting
confidence: 90%
“…family [2][3][4][5][6][7][8][9][10][11][12][13][14] were performed, including the investigation of van der Waals heterostructures. [15][16][17][18][19][20][21][22][23][24][25][26] In particular, due to the extreme stability of the fabricated MoSi 2 N 4 films in air, the materials can be used in sub-5-nm metal-oxidesemiconductor field-effect transistor (MOSFET) devices. 27 It was shown that due to the suitable band gap (1.42 eV), a high absorption coefficient, and spectroscopic limited maximum efficiency the MoGe 2 N 4 compound can be used for photovoltaic application.…”
Section: Introductionmentioning
confidence: 99%